Endolymphatic Potential Measured From Developing and Adult Mouse Inner Ear - Li, Yi; Liu, Huizhan; Zhao, Xiaochang; He, David Z. (Frontiers in Cellular Neuroscience, 2020)
The mammalian inner ear has two major parts, the cochlea is responsible for hearing and the vestibular organ is responsible for balance. The cochlea and vestibular organs are connected by a series of canals in the temporal bone and two distinct extracellular fluids, endolymph and perilymph, fill different compartments of the inner ear. Stereocilia of mechanosensitive hair cells in the cochlea and vestibular end organs are bathed in the endolymph, which contains high K+ ions and possesses a positive potential termed endolymphatic potential (ELP). Compartmentalization of the fluids provides an electrochemical gradient for hair cell mechanotransduction. In this study, we measured ELP from adult and neonatal C57BL/6J mice to determine how ELP varies and develops in the cochlear and vestibular endolymph. We measured ELP and vestibular microphonic response from saccules of neonatal mice to determine when vestibular function is mature. We show that ELP varies considerably in the cochlear and vestibular endolymph of adult mice, ranging from +95 mV in the basal turn to +87 mV in the apical turn of the cochlea, +9 mV in the saccule and utricle, and +3 mV in the semicircular canal. This suggests that ELP is indeed a local potential, despite the fact that endolymph composition is the same. We further show that vestibular ELP reaches adult-like magnitude around postnatal day 6, approximately 12 days earlier than maturation of cochlear ELP (i.e., endocochlear potential). Maturation of vestibular ELP coincides with the maturation of vestibular microphonic response recorded from the saccular macula, suggesting that maturation of vestibular function occurs much earlier than maturation of hearing in mice.